P120 Ambient exposure to diesel traffic particles and cardio-respiratory outcomes in healthy and in COPD subjects: 'Oxford Street 2'. (14th November 2013) - Sinharay, R; Barratt, B; Rocha, JP; Meesang, W; Collins, P; Kelly, F; Chung, KF; Cullinan, P
Abstract : Introduction and Objectives: Chamber studies using reconstituted diesel exhaust with healthy volunteers have shown enhanced lung inflammation resulting in vascular dysfunction. We hypothesised that inhalation of ambient levels of diesel emissions (DE) in patients with COPD or ischaemic heart disease (IHD) would induce oxidative stress with an acute airway inflammatory response and up-regulation of systemic inflammatory responses, reflected in abnormal cardiovascular physiology. Methods: Using a randomised, cross-over design, healthy non-smoking volunteers (n = 40) and patients with Stage 2 COPD (n = 40) are invited to walk in Oxford Street (only diesel traffic) and, on a separate occasion 3–8 weeks later, in Hyde Park, London. Personal particulate and gaseous exposures are measured in real time. Following baseline measurements, participants walk for two hours in either exposure location; a series of cardio-respiratory measurements are performed at intervals during and after each exposure. Here we report lung function and arterial stiffness measurements in the first 20 volunteers (10 with COPD). Findings: Compared to Hyde Park, exposures in Oxford Street had higher levels of black carbon (7.5μm/m 3 vs . 1.2μm/m 3, p < 0.001), and ultrafine particle counts (28692/cm 3 vs. 4989/cm 3, p < 0.001). In comparison with Hyde Park, healthy volunteers had a mean fall in FEV1 from baseline of -1.9% (p = 0.04) one hour after arrival in Oxford street; at 22 hours they had a mean decline of -8% (p = 0.03). In contrast, there were no significant differences in FEV1 responses in volunteers with COPD, though there was a mean drop in FVC of -8% (p = 0.03) two hours after the start of exposure in Oxford street compared to Hyde Park. We recorded no changes in arterial stiffness in either group for either exposure site. Conclusions: These early findings suggest that the observations made in healthy volunteers from chamber studies can be replicated in ambient conditions. The apparent lack of any respiratory response in patients with COPD may reflect their up-regulated baseline inflammatory state, or systematic differences in the exposure differential between the two sites. We continue to recruit volunteers; further measurements including markers of oxidative stress in sputum, serum, and small airways impedance are under way. Funded by the British Heart Foundation.